Association Between Carbohydrate Quality Index and Dietary Patterns, Sleep Quality, Anxiety Level, and Depression Symptoms: a Cross-Sectional Study - Yuksel, Aysun; Yilmaz-Onal, Hulya; Basturk, Berrak; Yalcin, Bahar (Soc Chilena Nutricion, Bromatologia & Toxicologia, 2022)
Aim: This study was conducted to determine the relationship between carbohydrate quality and sleep quality, depression, anxiety, stress and anthropometric measurements. Methods: The carbohydrate quality was calculated using the total fiber intake, ratio of whole grains to total grains, the ratio of solid carbohydrates to total carbohydrates, and the glycemic index. Sleep status was determined using the Pittsburgh Sleep Quality Index (PSQI) and nutritional status was determined by taking a 1-day food consumption record and food consumption frequency. Results: It was found that 20% of the participants with the highest carbohydrate quality had the highest sleep quality and the lowest body mass index. Conclusion: Adults should be informed that the quality of carbohydrates that they consume, was associated with better sleep quality and some micronutrients (potassium, magnesium, vitamin A-D-K-C-81-86, Folate) but no significant correlation was found between anxiety, depression, and stress scores
YUKSEL, AYSUN/0000-0002-6580-0207; Erguden, Berrak/0000-0001-6817-3141; Yalcin, Bahar/0000-0003-4036-7096
Keywords: Carbohydrate Quality; Fiber; Glycemic Index; Sleep Quality; Solid Carbohydrates; Total Carbohydrates; Whole Grain